Răspuns :
2x+2+3=1
2x+5=1
2x=1-5
2x=-4
x=-2
3x=11
x=11/3
2x-6+6x+3=5x+4x+8
3x=11
x=11/3
la modul rezolvi cela doua ec
x-3=4 si
x-3=-4 solutia negativa este
x=-1
2x+5=1
2x=1-5
2x=-4
x=-2
3x=11
x=11/3
2x-6+6x+3=5x+4x+8
3x=11
x=11/3
la modul rezolvi cela doua ec
x-3=4 si
x-3=-4 solutia negativa este
x=-1
a)x+1/3+1/2=1/6
numitor comun 6
6x/6+2/6+3/6=1/6 inmultim totul cu 6
6x+5=1
6x=-4
x=-4/6
x=-2/3
b)3x=11
x=11/3
c)2(x-3)+3(2x+1)=5x+4(x+2)
2x-6+6x+3=5x+4x+8
8x-9x=8+3
- x=11 inmultim cu -1
x=-11
d)Ix-3I=4
x-3=4
x=7
numitor comun 6
6x/6+2/6+3/6=1/6 inmultim totul cu 6
6x+5=1
6x=-4
x=-4/6
x=-2/3
b)3x=11
x=11/3
c)2(x-3)+3(2x+1)=5x+4(x+2)
2x-6+6x+3=5x+4x+8
8x-9x=8+3
- x=11 inmultim cu -1
x=-11
d)Ix-3I=4
x-3=4
x=7